Enhanced morphological diagnosis in infective endocarditis by transoesophageal echocardiography. Issue 2 (February 1990) - Taams, M A; Gussenhoven, E J; Bos, E; de Jaegere, P; Roelandt, J R; Sutherland, G R; Bom, N
Abstract : Thirty three consecutive patients with clinically suspected endocarditis were studied by both precordial cross sectional echocardiography and transoesophageal echocardiography. The diagnostic value of both techniques was assessed. The data were compared with findings at operation in 25 patients. In 21 patients with native valve endocarditis precordial echocardiography showed evidence of vegetations in six patients and suggested their presence in nine. Transoesophageal echocardiography identified vegetations in 18 patients. Complications were seen in four patients at precordial echocardiography and in nine patients at transoesophageal echocardiography. Precordial echocardiography did not show vegetations in any of the 12 patients with prosthetic valve endocarditis whereas transoesophageal echocardiography showed vegetations in four. Complications were seen in four patients at precordial echocardiography and in 10 at transoesophageal echocardiography. Echocardiographic findings were confirmed at operation in all 25 operated patients. In two patients both echocardiographic techniques had missed the perforation of the cusps of the aortic valve that was seen at operation, but this had no effect on patient management. Transoesophageal echocardiography is the best diagnostic approach when infective endocarditis is suspected in patients with either native or prosthetic valves.